REMOTE WORK SYSTEM AND LECTURERS’ PERFORMANCE IN ABIA STATE UNIVERSITIES, NIGERIA (Journal of the Management Sciences, 2025)
This study examined the relationship between remote work systems and lecturers’ performance in Abia State universities, Nigeria. Specifically, it investigated the relationship between technological infrastructure and service delivery, as well as between flexible work schedules and employee commitment. A survey research design was adopted, and data were collected from lecturers at Michael Okpara University of Agriculture, Umudike, and Abia State University, Uturu. The study population comprised 2,246 lecturers, and a sample size of 340 was determined using the Taro Yamane formula. Data were analyzed using descriptive statistics, while hypotheses were tested with the Pearson Product Moment Correlation. Findings revealed a significant positive relationship between technological infrastructure and service delivery, and between flexible work schedules and employee commitment. The study concludes that effective implementation of remote work systems can enhance lecturer performance if supported by adequate technological and institutional frameworks. It recommends that university management invest in digital infrastructure, training, and support systems to strengthen remote work practices and improve staff performance.
Keywords: Technological Infrastructure; Service Delivery; flexibility in work schedule; employee commitment; Remote Work System; Lecturers Performance.